The thin space between individuals and contexts as affordance for healthy longevity: a psychological perspective for aging in place studies - Butti, Stefania; Morganti, Francesca (Frontiers in Aging, 2025)
It seems likely that the growing number of older adults and increasing urbanization will be among the most significant demographic and societal trends in the near future. These two global phenomena will undoubtedly have a profound effect on the demographic and geographical makeup of our world. In view of these changes, it is crucial that the health and social sciences consider how the concept of Aging in Place could play a valuable role in longevity studies. Considering this topic as correlated to different important themes such as functional, symbolic, and emotional attachment and importance of homes, neighborhoods, and communities - resumed in the categories of people, place and time - we introduce a new perspective in Aging in (urban) Place studies from a psychological perspective based on situated and embodied cognition, with the purpose of deeply analyzing the thin space between people and their context, viewing place not as a neutral backdrop but as a continuous opportunity for individuals to act. Only through an analysis of urban spaces as limits or possibilities in everyday life can we grasp how the city can be an adequate place to empower individuals’ healthy longevity.